Detailed analysis of the African green monkey model of Nipah virus disease. - Sara C Johnston; Thomas Briese; Todd M Bell; William D Pratt; Joshua D Shamblin; Heather L Esham; Ginger C Donnelly; Joshua C Johnson; Lisa E Hensley; W Ian Lipkin; Anna N Honko (PLoS ONE, 2015)
Henipaviruses are implicated in severe and frequently fatal pneumonia and encephalitis in humans. There are no approved vaccines or treatments available for human use, and testing of candidates requires the use of well-characterized animal models that mimic human disease. We performed a comprehensive and statistically-powered evaluation of the African green monkey model to define parameters critical to disease progression and the extent to which they correlate with human disease. African green monkeys were inoculated by the intratracheal route with 2.5 × 10(4) plaque forming units of the Malaysia strain of Nipah virus. Physiological data captured using telemetry implants and assessed in conjunction with clinical pathology were consistent with shock, and histopathology confirmed widespread tissue involvement associated with systemic vasculitis in animals that succumbed to acute disease. In addition, relapse encephalitis was identified in 100% of animals that survived beyond the acute disease phase. Our data suggest that disease progression in the African green monkey is comparable to the variable outcome of Nipah virus infection in humans.